Practical Aspects of Declarative Languages 13th International Symposium, PADL 2011, Austin, TX, USA, January 24-25, 2011. Proceedings - Rocha, Ricardo; Launchbury, John.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 13th International Symposium on Practical Aspects of Declarative Languages, PADL 2011, held in Austin, TX, USA, in January 2011, co-located with POPL 2011, the Symposium on Principles of Programming Languages. The 17 revised full papers presented together with one application paper were carefully reviewed and selected from 40 submissions. The volume features a variety of contributions ranging from message-passing and mobile networks, concurrent and parallel programming, event processing and reactive programming, profiling and portability in Prolog, constraint programming, grammar combinators, belief set merging and work on new language extensions and tools.
Keywords: Computer science; Software engineering; Logic design; Artificial intelligence; Computer Science; Programming Languages, Compilers, Interpreters; Programming Techniques; Logics and Meanings of Programs; Software Engineering; Mathematical Logic and Formal Languages; Artificial Intelligence (incl. Robotics).